Minimum biopsy set for HER2 evaluation in gastric and gastro-esophageal junction cancer - Gullo, Irene; Grillo, Federica; Molinaro, Luca; Fassan, Matteo; De Silvestri, Annalisa; Tinelli, Carmine; Rugge, Massimo; Fiocca, Roberto; Mastracci, Luca (Endoscopy International Open, 2015)
Background and study aims: The HER2 status of small endoscopic biopsies is important for predicting the eligibility of patients with metastatic HER2-positive gastric cancer or gastro-esophageal junction (GEJ) cancer for anti-HER2 therapy approved by the U.S. Food and Drug Administration. The aim of this study was to identify the minimum biopsy set required to evaluate the HER2 status with confidence.Patients and methods: A total of 103 consecutive patients with resected gastric cancer or GEJ cancer were retrospectively selected; 2 formalin-fixed, paraffin-embedded samples of each surgical specimen and all paired endoscopic biopsies were analyzed for HER2 status with both immunohistochemistry (IHC) and fluorescent in situ hybridization (FISH) methods. A total of 10 virtual biopsies were constructed by selecting areas 2.6 mm in diameter on the luminal side of digitalized slides obtained from the surgical specimens. The results of evaluating HER2 status in virtual biopsies, slides containing complete surgical specimens, and endoscopic biopsies were compared. The resulting minimum biopsy set was applied to the endoscopic biopsy series for validation.Results: A biopsy set containing a minimum of 5 samples was identified as the most accurate in predicting HER2 status (sensitivity, 92 %; specificity, 97 %). In only 3 of the 103 cases (2.9 %) did a comparison of the HER2 evaluation of virtual biopsies and that of entire slides show inconsistent results. Overall agreement between the endoscopic biopsies and surgical samples for HER2 IHC status increased from 78.4 % to 92.3 % when biopsy sets containing 4 or fewer samples were compared with biopsy sets containing 5 or more samples.Conclusions: Although the recommendations suggest that 8 to 10 biopsies are necessary, the results show that a minimum set of 5 biopsies may be sufficient for reliable HER2 assessment in gastric cancer and GEJ cancer. However, endoscopists should be aware that a smaller sample size may be less accurate in selecting patients eligible for anti-HER2 therapy.